LIFESKILL KEPEMIMPINAN PENGEPUL BARANG BEKAS UJANG JALAN RAJAWALI SAKTI KELURAHAN DELIMA KECAMATAN TAMPAN PEKANBARU - Abdi, Jeki; Achmad, Said Suhil; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: in this research Issue is how leadership lifeskills in the barn Thrift Pengepul Melissa. This research aims to discover how leadership processes carried out in the barn Thrift Pengepul Melissa benefits from this study are expected to provide input or an idea to the students, the professors and all the readers and semuakalangan in order to be wise in addressing issues specifically related to the thrift collector (pengepul) around us. In addition to providing related information second-hand pengepul in this study, can be set as material to be learned later on apply positive values by other individuals in particular communities which have the same profession. This study used a qualitative approach to the types of descriptive. The technique of selection of informants in this study i.e., purposive sampling techniques. Informants in this study is that people who have the information required in the research because the informant is a person who is master of the matter will be researched. Data collection techniques used documentation, observation, interview and triangulation of Thrift Pengepul Leadership Lifeskills Ujang Milky Eagle Road In the village of the subdistrict of Pekanbaru Handsome Pomegranate. From the results of research conducted can be concluded that: 1) those involved in the barn Thrift Pengepul Melissa namely (1) Jeremy as Chairman (2) Thump Anisa Treasurer while the wife of Jeremy (3) Andre as an employee of Handyman sort items (4) Anto as a freight sorter employees (5) Aris as a freight sorter employees (6) Madan as builders cut employees (7) AR as an employee of the welder (9) Iron Man as an employee of the welder and iron (10) Ben as an employee the driver of the car. In the process of work in the warehouse uijang own, almost all decisions are left up to the employees, and because the leadership of the sendri else have other jobs. However, the leaders did not give authority to its employees, all decisions are indeed handed over entirely to the karyawa, but all that work must be in accordance with semana.Keywords: Leadership Lifeskills Thrift Pengepul